2017
DOI: 10.18203/2320-6012.ijrms20171852
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological spectrum of ovarian tumours from a referral hospital in Kashmir valley, Jammu and Kashmir, India

Abstract: Background: Ovary is a complex structure and its neoplasms show a wide spectrum of histological types and clinical behaviour. The present study was done with the aim of studying the histopathological pattern of the ovarian tumours in women of various age groups.Methods: This was prospective study conducted over a period of 2 years from Jan 2015 to Dec 2016 and included 193 cases of ovarian neoplasms.Results: Of 193 cases 155 (80.3%) were benign, 8 (4.1%) were borderline and 30 (15.5%) were malignant tumours. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 5 publications
6
12
0
Order By: Relevance
“…Sheikh S et al in her study found maximum cases in 21-40 years of age group similar to that seen in our study [27]. Peak age for benign tumours were seen in 3rd to 4th decade, which is similar to study done by Dhakal R et al and Sawant A et al [28,29].…”
Section: Discussionsupporting
confidence: 91%
“…Sheikh S et al in her study found maximum cases in 21-40 years of age group similar to that seen in our study [27]. Peak age for benign tumours were seen in 3rd to 4th decade, which is similar to study done by Dhakal R et al and Sawant A et al [28,29].…”
Section: Discussionsupporting
confidence: 91%
“…In current study among 84 neoplastic lesions, 74(88%) cases were benign, 3(3.6%) cases were of borderline nature while 7(8.4%) cases were malignant. This is in synchrony with the study of Sheikh et al N Gupta et al [30,31] while contradictory to study by Ahmad Z et al where malignant lesion was comparatively high(40.6%) [32].…”
Section: Discussionsupporting
confidence: 80%
“…However, the germ cell tumor (21.3%) was the second most encountered ovarian tumors in our locality . This report is in contradiction with reports from India by Sheikh et al [30], Lagos by Onyiaorah et al where germ cell tumor was the most common ovarian lesion followed by surface epithelial tumors [33]. Pilli et al reported that ovarian epithelial surface tumors accounted for 70.9% of all ovarian tumors; this is followed by germ cell tumors constituting 21.2%.…”
Section: Discussionmentioning
confidence: 56%
“…Ovary is subjected to monthly endocrine and traumatic insults during normal ovulatory cycles and becomes susceptible to tumorogenesis. 7 The concept of a fallopian tube origin for high grade serous carcinomas arose initially from studies on women with BRCA1/2 germline mutations who were discovered at the time of prophylactic salpingooophorectomy to have areas of marked epithelial atypia in their fallopian tubes. The lesions, called serous tubal intraepithelial carcinoma(STIC), have since been described in association with spontaneous high grade serous carcinoma arising from the fallopian tube.…”
Section: Discussionmentioning
confidence: 99%